A Robust One‐Compartment Fuel Cell with a Polynuclear Cyanide Complex as a Cathode for Utilizing H2O2 as a Sustainable Fuel at Ambient Conditions. Issue 35 (19th July 2013) - Yamada, Yusuke; Yoneda, Masaki; Fukuzumi, Shunichi
Abstract A robust one‐compartment H2O2 fuel cell, which operates without membranes at room temperature, has been constructed by using a series of polynuclear cyanide complexes that contain Fe, Co, Mn, and Cr as cathodes, in sharp contrast to conventional H2 and MeOH fuel cells, which require membranes and high temperatures. A high open‐circuit potential of 0.68 V was achieved by using Fe3[{CoIII(CN)6}2] on a carbon cloth as the cathode and a Ni mesh as the anode of a H2O2 fuel cell by using an aqueous solution of H2O2 (0.30 M, pH 3) with a maximum power density of 0.45 mW cm−2. The open‐circuit potential and maximum power density of the H2O2 fuel cell were further increased to 0.78 V and 1.2 mW cm−2, respectively, by operation under these conditions at pH 1. No catalytic activity of Co3[{CoIII(CN)6}2] and Co3[{FeIII(CN)6}2] towards H2O2 reduction suggests that the N‐bound Fe ions are active species for H2O2 reduction. H2O2 fuel cells that used Fe3[{MnIII(CN)6}2] and Fe3[{CrIII(CN)6}2] as the cathode exhibited lower performance compared with that using Fe3[{CoIII(CN)6}2] as a cathode, because ligand isomerization of Fe3[{MIII(CN)6}2] into (FeM2)[{FeII(CN)6}2] (M=Cr or Mn) occurred to form inactive FeC bonds under ambient conditions, whereas no ligand isomerization of Fe3[{CoIII(CN)6}2] occurred under the same reaction conditions. The importance of stable Fe2+N bonds was further indicated by the high performance of the H2O2 fuel cells with Fe3[{IrIII(CN)6}2] and Fe3[{RhIII(CN)6}2], which also contained stable Fe2+N bonds. The stable Fe2+N bonds in Fe3[{CoIII(CN)6}2], which lead to high activity for the electrocatalytic reduction of H2O2, allow Fe3[{CoIII(CN)6}2] to act as a superior cathode in one‐compartment H2O2 fuel cells.